Protection of the Rights of Secured Creditors Who Reject the Composition in the Suspension of Debt Payment Obligations: An Analysis of Articles 281 and 286 of the Law on Bankruptcy and Suspension of Debt Payment Obligations from the Perspective of Legal Politics and Legal Certainty - Biner Sihotang (Dinasti Research, 2026)
This research analyzes the legal position of secured creditors who reject the composition in the Suspension of Debt Payment Obligations (PKPU) process, particularly in relation to the normative conflict between the Law on Mortgage Rights (UUHT) and the Law on Bankruptcy and Suspension of Debt Payment Obligations (UUK PKPU). The UUHT provides absolute protection through the principles of droit de préférence and droit de suite, whereas the PKPU limits these rights through the stay period and the voting mechanism of the composition plan. Tension arises when secured creditors who reject the composition remain bound by the voting outcome, even though their rights originate from proprietary security rights that constitute real rights. By using a normative juridical method enriched with a legal hermeneutic approach, a limited comparative analysis, and a legal-political analysis, this research finds that Articles 281 and 286 of the UUK PKPU do not provide adequate protection mechanisms for secured creditors. The minutes of the Working Committee of the House of Representatives of the Republic of Indonesia (DPR-RI) in 2004 indicate that the lawmakers did not intend to downgrade the status of proprietary rights; thus, the current normative design of the PKPU creates a legislative gap that deviates from the original objectives of its formation. The lack of synchronization between the Law on Mortgage Rights (UUHT) and the Law on Bankruptcy and Suspension of Debt Payment Obligations (UUK PKPU) creates legal uncertainty, undermines substantive justice, and has serious implications for the investment climate and national financial stability. This research recommends regulatory harmonization through objection procedures, opt-out mechanisms, protection of collateral value, and the revision of Article 286 of the UUK PKPU to align with the principles of proprietary rights and international standards of creditor protection. Keywords: Mortgage rights, legal certainty, secured creditors, Suspension of Debt Payment Obligations (PKPU)